Penggunaan Pidana Denda dalam Perundang- undangan - Syaiful Bakhri (Fakultas Hukum Universitas Islam Indonesia, 2002)
The application of fine on the national criminal law perspective have got significant progress. It is indicated by the acceptance of philosophy of conmdemnation about fine anda progress from the way of realization forits, conmdemnation by using the variouskinds of models introduced, but the glowof this application for fine have not been satisfied entirely because the trend is that sentence law forcn'minalis stiil applied sentence law as acommon law. That is why it need to launch the new thoughts as the break through inorder that the functionalization of conceptof fine is acceptable as the preventive alternatives for crime prospectively